A New Unity-Gain 5-Level Active Neutral-Point-Clamped (UG-5L-ANPC) Inverter - Lee, Sze Sing; Lim, Chee Shen; Siwakoti, Yam P.; Idris, Nik Rumzi Nik; Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (CENCON 2019 - 2019 IEEE Conference on Energy Conversion, 2019)
The active neutral-point-clamped (ANPC) inverter is a popular multilevel inverter for various industry applications. In a recent attempt, an improved topology that integrates a flying capacitor to enhance the voltage gain from half to unity has been presented [11]. Retaining the benefit of unity-gain, this paper proposes a new ANPC topology with two improvements. Firstly, the voltage stress of the flying capacitor is reduced by half. Secondly, the charging of the flying capacitor at 0 level is made possible to achieve uniform charging over the power cycle. Comprehensive analysis is presented and experimental results of a prototype are presented for validation. Finally, the extension of the topology with increased number of output voltage levels generation is briefly discussed.
Keywords: Active neutral point clamped; Comprehensive analysis; Flying capacitor; Industry applications; Multilevel inverter; Output voltages; Voltage gain; Voltage stress; active neutral-point-clamped inverter; five-level; flying capacitor; multilevel inverter; unity-gain